FACTORS AFFECTING THE FORMATION OF STUDENTS' COMPETENCE TO UNDERSTAND HISTORICAL REALITY AND EXPLAIN IT IN LOGICAL COHERENCE (American Journal of Research in Humanities and Social Sciences, 2023)
In this article Factors affecting the formation of students-young people's ability to understand historical reality and explain it logically, development of historical thinking, maturation as a mature person with intellectual potential through pedagogical and psychological means of growing students as professionals development is covered.